Analisis Brand Awareness Terhadap Brand Attitude Handphone Merek Nokia - Maisirata, Pasifikus (MABIS, 2011)
In this recent years, there has been competition between mobile phone in Indonesia. The producers create a high quality and creative mobile phone that will be useful and friendly for consumer. One of them is Nokia, as the marker leader of mobile phone in Indonesia, has a declining market segment because of emerging a competitor for Nokia, that is Sony Ericsson. Nokia has conducted some action so that consumer will decide their purchase for Nokia. The aim of this research is to analyze the effect of quality, price, and distribution factors to purchase decision of Indomie. This research involves 100 college student in STIE Widya Dharma as its respondent and employ accidental sampling as its sampling method. Author distributes quetionaire for data collection and analyzes it with double-regression linear analysis by SPSS software. The result of regression test shows that quality, price, and distribution variables have a significant and positive effect to purchase decision of Indomie. They are 0,404, 0,396, 0,321, respectively. The adjusted R2 of 0,626 explain that 62,6% of purchase decision variable can be explained by quality, price, and distribution variable, while the rest of 37,4% is affected by other variable which is not included in this research